TEKNOLOGI INTERNET OF THINGS DALAM PROSES MONITORING SUHU DAN KELEMBABAN DI GUDANG PENYIMPANAN BAHAN KULIT - asep saepudin (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The company's business competition is getting tougher in today's digital era. So that a company is required to adapt to technological advances. The Internet of Things has begun to be implemented to realize industry 4.0. One of the foundations of industrial revolution 4.0 is IoT. So that IoT can be used in the process of monitoring temperature and humidity in leather storage warehouses so that skin quality can be maintained. High and low humidity greatly affects the quality of the skin. IoT devices that are continuously connected to the internet network can provide convenience for remote monitoring. In addition, it can help warehouse supervisors to work efficiently and effectively and decide an action based on historical data obtained from monitoring results. An IoT-based temperature and humidity monitoring system connected to MQTT (Message Queuing Telemetry Transport) can send data or messages in real-time so that if there is an increase in temperature and humidity beyond a predetermined threshold, supervisors can immediately take action.